Economic performance of bio-gas plant in the context of Bangladesh - Paul, Dilip Kumar; Karim, A.N. Mustafizul (1999)
For a country like Bangladesh large proportions of the rural population and the urban poor depend and will continue to depend on the low quality energy sources such as firewood for cooking and kerosene for lighting. The conventional paradigm of development characterized by commercial energy supply oriented policies may not come true in the foreseeable future. Long term sustainable development of the country should, therefore, require a gradual shift towards renewable sources of energy as they are more evenly distributed and environmentally less destructive. In this context bio-gas plant could be a promising source of energy with the prospect of increasing its energy supplies in a self-reliant way. The present study was conducted to evaluate the economic viability of such plants. This study could be helpful in decision making to take up a program of mass-scale implementation of bio-gas plants. Some commonly used economic indicators were evaluated and sensitivity analysis was also performed. Through the analysis it was revealed that increasingly higher capacity plants were found to be superior in the context of economic performance. The findings suggest that bio-gas plant could be considered as an alternative source in formulating the future national energy plan.